'If You call 911 they are going to kill me': families' experiences of mental health and deaths after police contact in the United States. (2nd July 2020) - Baker, David; Pillinger, Claire
ABSTRACT: This paper examines families' perceptions of deaths after police contact of persons with mental illnesses (PMIs) in the United States. It uses qualitative semi-structured interviews with the bereaved family members of citizens who died after police contact in the US in the period 1999–2015. The paper considers the factors that led to their death, and how families perceive police actions led to the death of their loved one. The paper uses three key tenets of policing identified by Bittner [1975. The functions of the police in modern society: a review of background factors, current practices and possible role models . New York, NY: Aronson] as a framework in aiming to understand how police interactions with PMIs can lead to deaths. It discusses how police have become a de facto response to a healthcare issue and how the use of force appears to be linked with these interactions. Interventions such as enhanced training and the implementation of Crisis Intervention Teams (CITs) are assessed in terms of families' perceptions of their capacity to improve the outcomes of police interactions with PMIs. The paper concludes that the policing of PMIs in the US is problematic, and can result in the deaths of citizens.